Giant Precordial T Wave Inversion in a Patient with Gastroenteritis. (12th September 2011) - Rott, David; Leibowitz, David; Weiss, A. Teddy
Abstract : Giant precordial T wave inversion (GPTI) on ECG may be the result of several pathologies, including myocardial ischemia, pulmonary edema, pulmonary embolism, subarachnoid hemorrhage, apical hypertrophy, and postpacing. We describe a case of a 75-year-old woman who developed GPTI after an episode of gastroenteritis. To our knowledge, this is the first report of this ECG pattern associated with gastroenteritis.